MODELLING THE EFFECTS OF SOCIO-ECONOMIC DEMOGRAPHICS ON URBAN WATER USAGE IN KOTA SAMARAHAN, SARAWAK : A NEW EDUCATION HUB IN BORNEO ISLAND - Kuok, King Kuok; Chiu, Po Chan; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri; Chin, Mei Yun (Penerbit UMT, 2023)
This study was carried out to investigate the influence of socio-economic status on household water usage patterns in Kota Samarahan, which is an education hub in Sarawak, Malaysia. This study commenced with a random sampling of 200 respondents, categorised into low-, medium- and high-income households. The medium-income household category was found to have the highest amount of water usage. The results showed that an increase in income leads to an increase in socio-economic status, dwelling size, and household occupancy. It was also observed that the “numbers of children” influences the increase in water usage within a family. In addition, the data set was further analysed using multiple linear regression modelling (STEPWISE). It was found that an increase in socio-economic demographic factors, including education level, number of female adults, number of clothing washed daily, number of wage earners, and number of dishes washed daily, increased the water usage per household. The findings of this study are crucial to ensuring a sustainable urban water supply in Kota Samarahan.